UNDERSTANDING THE IMPACT OF AI-BASED DECISION SUPPORT (CHATGPT) ON INVESTMENT DECISIONS: A MODERATED MODERATION ANALYSIS OF FINANCIAL LITERACY AND ETHNIC IDENTITY IN BANDUNG - Putri, Rafa; Syawal, Erik; Gunardi, Ardi; Juju, Undang (Faculty of Economic and Business, University of Pasundan, 2026)
This study examines the influence of Artificial Intelligence (ChatGPT) usage on investment decision-making by considering the moderating roles of financial literacy and ethnic identity among investors in Bandung, Indonesia. Employing a quantitative approach through Structural Equation Modeling–Partial Least Squares (SEM-PLS) using SmartPLS 4.0, the study involved 119 respondents who have utilized ChatGPT in their investment processes. The results indicate that ChatGPT usage has a positive and significant effect on investment decisions. However, financial literacy does not significantly moderate this relationship. Conversely, ethnic identity demonstrates a second-order moderating effect, wherein Sundanese investors consistently experience a significant influence of ChatGPT on investment decisions regardless of their financial literacy level. These findings highlight the importance of cultural values in the adoption of AI technologies. The study’s limitations include a narrow geographical scope, suggesting that future research should expand to diverse ethnic contexts and incorporate additional behavioral variables. The results offer insights for technology developers, financial educators, and regulators in designing culturally sensitive financial and technological education initiatives.